Legal and regulatory reforms to enhance the Nigerian environment (2012)
Recent events around the world have made humans more conscious of the environment in which they live. Since the environment is not subject to human command, attention must focus on how to use the instrumentality of the law, a potent weapon of social control, to regulate human activities that abuse the environment and unleash devastating consequences on the entire ecosystem. This work is a survey of efforts at enhancing the quality of life in Nigeria viewed from the prism of environmental law. It highlights constitutional provisions, statutory enactments and institutional framework, and judicial remedies that seek to protect the environment. The work also offers useful suggestions on how to ameliorate the deplorable environmental situation in Nigeria by improved enforcement of extant laws, efficient coordination of relevant government agencies, effective utilization of delegated legislative authority, reform of the legal landscape by conferment of statutory standing to sue in environment- related cases and the recognition of the right to a healthy environment as a constitutional right.